BMSCs-targeting piezoelectric stimulation and immunomodulatory dual-functional hydrogel for promoting diabetic bone regeneration - Jintao Dong; Wengang Dong; Huijie Ran; Dongxu Wu; Xinli Wang; Hongli Chen; Jiahao Cao; Xu Wang; Xinsen Lin; Wei Lei; Tianji Wang; Yafei Feng (Materials Today Bio)
Bone regeneration in diabetic patients poses a significant clinical challenge due to persistent hyperglycemia and chronic inflammation, which disrupt the crucial interaction between the immune microenvironment and bone marrow-derived mesenchymal stem cells (BMSCs), thereby impairing osteogenesis. To address this limitation, ultrasonic-responsive barium titanate (BTO) nanoparticles were coated with BMSC membranes (B-TNs) and subsequently integrated into a carboxylated modified silk fibroin (CMS) hydrogel. This resulted in a dual-functional B-TNs@CMS composite hydrogel designed to combine targeted BMSC stimulation with immunomodulatory properties. Under diabetic conditions, the composite hydrogel facilitated macrophage polarization from the pro-inflammatory M1 phenotype to the anti-inflammatory M2 phenotype. Proteomic analysis and validation assays demonstrated that CMS reprograms macrophages through the PI3K-Akt-mTORC1 signaling axis, thereby restoring an osteogenesis-supportive immune microenvironment conducive to osteogenesis. Simultaneously, the degradation of CMS released B-TNs, which produced a moderate level of reactive oxygen species (ROS) under optimized extracorporeal ultrasound (US) stimulation. This process activated Wnt/β-catenin signaling, enhancing BMSC proliferation and osteogenic differentiation. This study highlights the significant potential of a dual-modular strategy integrating immune modulation with spatially targeted osteogenic stimulation, offering a promising therapeutic approach for diabetic bone regeneration.